The Role of the Right Hemisphere in Emotional and Behavioral Disorders of Patients With Frontotemporal Lobar Degeneration: An Updated Review - Gainotti, Guido (Frontiers in Aging Neuroscience, 2019)
Two main models have been advanced to explain the asymmetries observed in representation and processing of emotions. The first model, labeled ‘the right hemisphere hypothesis’, assumes a general dominance of the right hemisphere for all emotions, regardless of affective valence. The second model, named ‘the valence hypothesis’, assumes an opposite dominance of the left hemisphere for positive emotions and of the right hemisphere for negative emotions. Patients with Fronto-temporal degeneration (FTD) could contribute to clarify this issue, because disorders of emotional and social behaviour are very common in this disease and because atrophies, affecting the antero-ventral parts of the frontal and temporal lobes can be clearly asymmetric in the early stages of this disease.The main scope of the present review therefore consisted in evaluating if results of investigations conducted on emotional and behavioural disorders of patients with right and left FTD support the ‘right hemisphere’ or the‘valence’ hypothesis. A thorough review of behavioural and emotional disorders in FTD patients found 139 possible studies, but only 24 papers met the requested criteria to be included in our review. All the 21 studies retained as relevant with respect to the ‘right hemisphere hypothesis’ supported the assumption of a general dominance of the right hemisphere for emotional functions, whereas only one of the 3 investigations considered as relevant with respect to the ‘valence hypothesis’ were in part consistent with this hypothesis, though being also open to interpretation in terms of the ‘right hemisphere’ hypothesis. This study, therefore, clearly supports the model of a general dominance of the right hemisphere for all emotions, regardless of affective valence.